The environment has rights: Eco-spiritual social work through ubuntu philosophy and Pachamama: A commentary - Chigangaidze, Robert K (SAGE Publications, 2022)
Ubuntu has launched the Global Agenda for Social Work and Social Development, 2020–2030. This commentary stipulates how ubuntu can reinforce the Pachamama rights and its significance to social work practice. The African philosophy of ubuntu has potential to enhance the framework of understanding environmental rights from an eco-spiritual social work perspective and integrating the concepts of Pachamama rights. Clearly showing the link between Pachamama and ubuntu, this paper reminds social workers to advance the Rights of Nature.